Glutathione content in erythrocytes and bone marrow of animals in mexidol use under the conditions of acute stress - Vlasenko, N. O. (Zaporozhye Medical Journal, 2013)
Acute immobilization stress and its pharmacological correction with mexidol (2-ethyl-6-methyl-3-oxypyridine succinate) were modeled in albino male rats. The drug was administered to animals in  dose 100 mg/kg before stress exposure with following investigation of content of glutathione and its fractions (GSH, GSSG) in different terms of post-stress period. It is shown that mexidol enhances the level of reduced glutathione (GSH) in erythrocytes as well as in myeloid tissue in terms from 3 hrs to 5 days after the stress. It also regularly increases common glutathione concentration in erythrocytes in alarm stage of stress-syndrome (3-24 hrs). Such effect of mexidol, probably, is the consequence of its direct antioxidant action which lowers the load on physiological antioxidant system and promotes the maintenance of normal functional activity of erythron’s central and peripheral parts in stress.